Meningkatkan kemampuan perkalian siswa kelas 2 SDN 003 Rantau Pulung menggunakan alat peraga Kelereng dan batu kerikil - Sugita, Sugita (IAIN Samarinda, 2014)
The objective of this study was to improve the students’ ability in counting as one of the mathematics lesson of the second grade students of SDN 003 Rantau Pulung through marbles and gravels. This is a classroom action research which has a goal to improve the quality of education. The instruments used in this study were a mathematics test and classroom observation. The criteria of success were (1) the students’ average score, 70, and (2) the students participation, 75%. The result of the study shows that in cycle 1, the criteria of success did not achieve yet. In cycle 2, it shows that the criteria of success has been fulfilled. It shows that 75% of the students were active in the teaching and learning process and the students’ average score can be improve from 58.50 in cycle 1 became 73.00 in cycle 2.